The founder's mentality : How to overcome the predictable crises of growth / Chris Zook, James Allen - Zook, Chris
Why is profitable growth so hard to achieve and sustain? Most executives manage their companies as if the solution to that problem lies in the external environment-find an attractive market, formulate the right strategy, win new customers. But when Bain & Company's Chris Zook and James Allen, authors of the bestselling Profit from the Core, researched this question, they found that 90 percent of the challenges to growth are internal: increasing distance from the front lines, loss of accountability, and proliferating processes and bureaucracy, to name only a few. More crucial is their finding that companies experience a set of predictable internal crises, at predictable stages, as they grow; and that for even the healthiest companies, these crises, if not managed properly, can stifle the company's ability to grow further-and actively lead it into decline.